Antiplatelet Therapy in High Risk Patients for Preeclampsia Prevention - Asiya Parveen Shaikh, Farhan Ahmed Shaikh, Tahmina Mahar, Shahneela Moosa, Sidrah, Rukhsana Saboor, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal was to determine if antiplatelet medication was effective at preventing preeclampsia in high risk patients as well as its negative effects. Study Design: Descriptive case series Place and Duration: Gynaecology and obstetrics department LUMHS Jamshoro. Jan 2022-Dec 2022 Methods: Total 135 pregnant females of age 20-40 years were included in this study. The included patients were all high risk pregnancies with parity 5, gestational age 12 weeks, and hospital prenatal checkups. Aspirin (an antiplatelet medication) 120 mg/day was administered to all the females. They were monitored in the OPD up until the 36th week of pregnancy. Preeclampsia was diagnosed in females who had BP > 140/90 mmHg and proteinuria > 300 mg using the urine dipstick technique. All data were examined using SPSS 24.0. Results: There were 95 (70.4%) cases had age <30 years and 40 (29.6%) females had age >30years. Mean parity of the females was 2.3±5.11. Mean BMI was 25.02±6.35 kg/m2. There were 60 (44.4%) females were educated and 55 (40.75) females were from urban areas. History or preeclampsia found in 7 (5.2%) cases. There were 28 (20.7%) females were obese, chronic hypertension found in 9 (6.75) cases, gestational hypertension in 92 (68.1%) cases and gestational diabetes in 22 (16.3%) cases. Frequency of preeclampsia was found in 19 (14.1%) cases. Other complications were low platelet, acid peptic disease and Antepartum haemorrhage. Conclusion: We observed that the occurrence of preeclampsia was extremely low among high-risk females who had 120mg of Aspirin (antiplatelet medication) in the first trimester, but that the negative effects of antiplatelet therapy increased with increasing doses. Keywords: Pregnant females, Gestational Hypertension, Antiplatelet Therapy, Preecplampsia